The role of intellectual capital in driving value creation: The case of Algeria Telecom (Ghardaia (Journal of Economic Additions, 2025)
This study analyzed the impact of intellectual capital (human, structural, customer) on value creation at Ghardaia branch of Algeria Telecom. Using a descriptive methodology and a questionnaire distributed to a sample of 56 employees, the research found varying degrees of intellectual capital application. The results demonstrated a significant positive impact of intellectual capital on value creation. However, this effect was primarily driven by human and customer capital. Structural capital's contribution was notably weak. The study concludes that value creation in this organization relies more on individual expertise and external relationships than on its internal systems and documented processes.Jel Classification Codes: J24, G32, L25, L96.
Keywords: intellectual capital, value, value creation, Algeria Telecom.